Stromal cell inhibition of anti-CD20 antibody mediated killing of B-cell malignancies - Fagnano, Ester; Pendharkar, Swati; Colton, Madyson; Jones, Philip N.; Sallan, Marta Crespi; Klymenko, Tetyana; Braun, Andrejs; Klein, Christian; Honeychurch, Jamie; Cheadle, Eleanor J.; Illidge, Timothy M. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The glycoengineered type II anti-CD20 monoclonal antibody obinutuzumab has been licensed for treatment in follicular non-Hodgkin lymphoma and B-CLL following clinical trials demonstrating superior outcomes to standard of care treatment. However, ultimately many patients still relapse, highlighting the need to understand the mechanisms behind treatment failure to improve patient care. Resistance to chemotherapy is often caused by the ability of malignant B-cells to migrate to the bone marrow and home into the stromal layer. Therefore, this study aimed to investigate whether stromal cells were also able to inhibit type II anti-CD20 antibody mechanisms of action, contributing to resistance to therapy. Methods: A stromal-tumor co-culture was established in vitro between Raji or Daudi B-cell tumor cells and M210B4 stromal cells in 24 well plates. Results: Contact with stromal cells was able to protect tumor cells from obinutuzumab mediated programmed cell death (PCD), antibody dependent cellular phagocytosis and antibody dependent cellular cytotoxicity. Furthermore, such protection required direct contact between stroma and tumor cells. Stromal cells appeared to interfere with obinutuzumab mediated B-cell homotypic adhesion through inhibiting and reversing actin remodelling, potentially as a result of stromal-tumor cell contact leading to downregulation of CD20 on the surface of tumor cells. Further evidence for the potential role of CD20 downregulation comes through the reduction in surface CD20 expression and inhibition of obinutuzumab mediated PCD when tumor cells are treated with Ibrutinib in the presence of stromal cells. The proteomic analysis of tumor cells after contact with stromal cells led to the identification of a number of altered pathways including those involved in cell adhesion and the actin cytoskeleton and remodeling. Discussion: This work demonstrates that contact between tumor cells and stromal cells leads to inhibition of Obinutuzumab effector functions and has important implications for future therapies to improve outcomes to anti-CD20 antibodies. A deeper understanding of how anti-CD20 antibodies interact with stromal cells could prove a useful tool to define better strategies to target the micro-environment and ultimately improve patient outcomes in B-cell malignancies.